Design and Implementation of a PI-Controlled Lithium Ion Battery Charger with Protection and Monitoring - Mollaei, Amir (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2020)
The importance of power electronics has been growing in recent decades and nowadays it is playing an undeniable important role in our everyday life. One of the most common application of power electronics is switching mode power supply. Those chargers for mobile phones and laptops, power supply for desktop computers, and uninterruptable power supplies are few examples of such converters. In this thesis work, a design and implementation of a PI controller for a switching power supply, that is specifically a Lithium-Ion battery charger, is presented. A brief review of rechargeable batteries and DC-DC converter is provided. Different control techniques for charging the Lithium-Ion battery is studied and constant-current/constant-voltage interpretation is employed in this study. Different topologies for DC-DC power conversion are compared and a half-bridge converter is designed and implemented as a prototype. A comprehensive description of protective mechanism and safety systems is provided. Moreover, a brief description for all the components that are used in this thesis is presented. The design of the control loop and PI compensator are investigated in details. The results of the stability analysis in form of step response and Bode plot are presented in simulations and experimental tests. In the conclusion it is indicated that the proposed digital controller can effectively eliminate the steady-state error with an excellent gain margin and phase margin improvements. Keywords: Battery Charger, Half-bridge converter, PI controller, Digital Controller.

ÖZ: Güç elektroniğinin önemi son yıllarda artmakta ve günlük yaşamımızda yadsınamaz önemli bir rol oynamaktadır. Güç elektroniğinin en yaygın uygulamalarından biri anahtarlamalı güç kaynağıdır. Cep telefonları ve dizüstü bilgisayarlar için olan şarj cihazları, masaüstü bilgisayarlar için güç kaynağı ve kesintisiz güç kaynakları, bu tür dönüştürücülerin birkaç örneğidir. Bu tez çalışmasında, anahtarlamalı bir güç kaynağı için bir PI denetleyicinin, özellikle bir Lityum-İyon pil şarj cihazına uygun tasarımı ve uygulaması sunulmuştur. İlk olarak, şarj edilebilir piller ve DC-DC dönüştürücü hakkında kısa bir inceleme sağlanmıştır. Daha sonra, lityum-İyon pilin şarj edilmesi için farklı kontrol teknikleri çalışılmış ve bu çalışmada sabit akım / sabit voltaj yorumlaması kullanılmıştır. DC-DC güç dönüşümü için farklı topolojiler karşılaştırılmışve bir yarım köprü dönüştürücü bir prototip olarak tasarlanıp uygulanmıştır. Buna ek olarak, bu tezde bulunan koruyucu mekanizma ve güvenlik sistemlerinin ve kullanılan tüm bileşenlerin kısa bir açıklaması sunulmaktadır. Kontrol döngüsü ve PI kompansatörünün tasarımı ayrıntılı olarak incelenmiştir. Stabilite analizinin adım tepkisi ve Bode grafiği şeklindeki sonuçları simülasyonlarda ve deneysel testlerde sunulmuştur. Sonuç olarak, önerilen dijital denetleyicinin kararlı durum hatasını mükemmel bir kazanç marjı ve faz marjı iyileştirmeleri ile etkili bir şekilde ortadan kaldırabileceği belirtilmiştir. Anahtar Kelimeler: Pil Şarj Cihazı, Yarım köprü dönüştürücü, PI denetleyici, Dijital Denetleyici
Master of Science in Electrical and Electronic Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Electrical and Electronic Engineering, 2020. Supervisor: Assist. Prof. Dr. Davut Solyalı.
Keywords: Electrical and Electronic Engineering; Switching power supplies--Design and construction--Electronics; Electronic apparatus and appliances--Power supply--DC-to-DC converters; Battery Charger; Half-bridge converter; PI controller; Digital Controller